Shaping organizational culture in psychiatric hospitals: the roles of values, leadership, and motivation - Mila Triana Sari; Miko Eka Putri; Jufri Al Fajri; Daryanto Daryanto (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Organizational culture is widely recognized as a central determinant of institutional effectiveness and quality services. The complexity of patients need in psychiatric hospital requires cohesive teamwork and strong commitment. The formation of organizational cultures was influenced by a variety of factors, but it has not been widely identified. Purpose: The study was investigated the influence of organizational values, leadership, and employee motivation in shaping the organizational culture of psychiatric hospitals. Method: A descriptive quantitative with cross-sectional approach. The study took place from June 2024 in H.M Syukur Mental Hospital. The independent variables studied were values, leadership, and motivation, while the dependent variable was organizational culture. Using purposivel sampling and slovin formula 87 respondents were selected, who meet specific inclusion and exclusion criteria. The analysis proceeded with a univariate test to determine the frequency distribution of respondents characteristics, followed by bivariate analysis using chi-square test. Results: The statistical test results show that all shaping factors are significantly related to organizational culture (p<0.05). Specifically, the values shaping factor has a significant relationship (p=0.003), the leadership factor also shows a significant relationship (p=0.001), and the motivation factor has a very significant relationship with organizational culture (p=0.000). These findings confirm that these three factors play an important role in shaping organizational culture. Conclusion: All three shaping factors—values, leadership, and motivation—are significantly associated with organizational culture, with motivation showing the strongest significance, confirming their key role in shaping it.